COMMERCIAL SEXUAL EXPLOITATION OF CHILDREN: AN EFFORT OF HANDLING AND LEGAL PROTECTION - Rahayu, Devi; Fatoni, Syamsul (Yustisia, 2019)
This article examines efforts to protect and deal with government, law enforcement agencies and assistants or NGOs in preventing and eradicating commercial sexual exploitation of children (CSEC). In Indonesia there are many child trafficking in border areas and cities like Surabaya, which are identified as sending, transit and destination cities. The research type used is  the juridical empirical study namely the effectiveness research of regulations enforcement on child protection. Primary data obtained from experience experienced by children and the family, law enforcement, government and companion Non Governmental Organization (NGO). Data collection techniques carried out by the interview method and FGD. The results showed that the commercial sexual exploitation of children is an act of human trafficking because the purpose of sexual action is to obtain money or other goods with the children, sex service users, liaison and related parties. The highest educated victims of Commercial Sexual Exploitation of Children (CSEC) are high school and are in an economically inadequate condition, broken home, and the influence of uncontrolled social media.